The Application Of Dividend Yield-Based Investment Strategyin The Indonesia Stock Exchange (Case Study Of Idx High Dividend 20 For The Period 2018-2022) - Muhammad Rizky Amin; Subiakto Soekarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The growth of the stock market in Indonesia has been rapid, in 2022 total of 10.3 million investors counted. To maximize their portfolios, investors seek simple and applicable investment strategies. One such strategy, based on dividend yield, is gaining popularity in the United States but remains underutilized in Indonesia. The Research aims to analyze the application of dividend yield-based investment strategies on the Indonesian stock exchange, particularly in the IDX High Dividend 20 stock index, to determine if it can produce results similar to the Dow Jones stock index. Historical data from 2018 to 2022 on IDX High Dividend 20 stocks, including closing prices at the end of the year and annual dividends, were used to calculate dividend yield and form a portfolio consisting of the top 10 stocks with the highest yield. This approach is called The Dogs of the Dow, where in this research, the other variants of the Dog of the Dows such as Dog of the Dows X (Dow 7), Top Low 5 (Dow 5), Top Low 4 (Dow 4), and Fund allocation 4 (Foolish 4) were utilized. Results show that dividend yield-based investment strategies are simple to apply and can provide high performance, making them a profitable option for investors. Keywords: Indonesian stock exchange, dividend yield, IDX high dividend 20, The Dogs of the Dow, and investment strategy.